Youth vs. adults: Analyzing mental health information seeking on social Q&A platforms during COVID-19 - Jiabao Pan; Yangjuan Hu; Xi Wang (Digital Health)
Objective The COVID-19 pandemic has deeply impacted mental health, especially among young people, driven by extended social isolation, routine disruptions, and uncertainties about health and the future. While rising levels of anxiety and depression in this group are well-documented, little is known about their online information-seeking patterns during this prolonged crisis. Exploring these patterns is vital for understanding how individuals navigate mental health challenges and seek support in times of uncertainty. Method This cross-sectional study investigates the online mental health information-seeking behaviors of young people in China during the COVID-19 pandemic. Using content analysis, we examined 1211 questions and 2303 responses from a popular Chinese social Q&A platform, Zhihu. Among these, 691 questions were identified as originating from young people, with the remainder attributed to adults. The analysis focused on the types of information sought, the effectiveness of responses, and the responsibility frameworks conveyed. By comparing the information-seeking behaviors of young people to those of adults, the study aims to uncover the unique needs of younger individuals. Findings First, young people primarily sought information about social adaptation, whereas adults demonstrated greater interest in diagnosis-related queries. Second, while young people's questions received more responses on average, nearly half remained unanswered for over four weeks, reflecting a lack of timely support. Finally, the qualitative nature of responses presented limitations, particularly for youth: they received more responses emphasizing individual responsibility and fewer recovery stories compared to adults, limiting exposure to systemic perspectives and hope-inspiring recovery pathways. Conclusions This study highlights the unique mental health information-seeking behaviors of young people in China and the potential of social Q&A platforms, offering valuable insights to help health professionals and policymakers allocate resources effectively and design targeted interventions to support this demographic during the pandemic.